The Impact on Dental Staining Caused by Beverages in Combination with Chlorhexidine Digluconate - Sarembe, Sandra; Kiesow, Andreas; Pratten, Jonathan; Webster, Corinne (European Journal of Dentistry, 2022)
Objectives There are several hypotheses regarding how chlorhexidine (CHX) digluconate causes staining with the role of beverages, specifically the precipitation of anionic dietary chromogens onto adsorbed cations, the most probable cause. The aim of this study was to investigate and compare the staining potential of common beverages using an in vitro staining and brushing model to better understand the interactions between chromogens from different beverage categories and the teeth.Materials and Methods Human enamel samples were exposed to a cyclic treatment of artificial saliva and 0.2% CHX mouthwash combined with a range of beverages, with and without brushing, simulating a period equivalent to 2 weeks. Eleven beverages were tested: diet coke, diet lemonade, white wine, red wine, lager beer, black tea, coffee, black tea with milk, coffee with milk, ginger and lemon infusion, and water. Toothbrushing was performed in a brushing simulator with toothpaste and also with water. Colorimetric differences were determined by ΔE using a VITA Easyshade dental spectrophotometer. Statistical analyses were performed by one-way analysis of variance with post hoc Tukey's honestly significant difference test and Levene's test.Results Black tea and red wine produced highest staining, which agrees with the literature. Significant staining was also observed for a ginger and lemon infusion, coffee, coffee with milk, tea with milk, and lager beer compared with water (p < 0.05). The staining potential of diet coke in combination with brushing appeared to be connected to its low pH. Both white wine and diet lemonade produced stain comparable to the water control. After treatment with high staining beverages, scanning electron microscope evaluation confirmed the formation of a surface layer. The mechanical resistance of the stain differed depending on the beverage, black tea stain was the most resistant. The addition of milk to tea and coffee considerably modified the stain layer and the adhesion to the tooth surface.Conclusion The data may help demonstrate that appropriate user guidance can avoid stain and in turn help improve user compliance during short-term use of this gold standard antimicrobial treatment.
Keywords: chlorhexidine; dental staining; beverages; color measurements; SEM